Gas turbine transient performance - heat soakage modelling - Naylor, Philip (Cranfield University, 2004)
The ability to accurately extract steady state performance information from transient engine test data has the potential to significantly reduce test bed time and cost, depending upon the accuracy with which engine phenomena such as heat soakage and transient tip clearance changes can be modelled within the context of a whole engine performance code. This thesis describes improvements to the GTTrans generic Whole engine performance code thermo mechanical heat soakage and tip clearance methods. This thesis describes the streams method in which a collection of definite volumes are used to represent engine component hardware and perform transient heat transfer calculations accounting for both conduction and convection to and from non-trivial engine component geometries. Transient metal and gas temperature profiles are then used to estimate transient blade tip clearances. The streams method has been incorporated into a Rolls-Royce Trent 500 engine performance code. Accounting for heat soakage, tip clearances, and bleed temperature Variations within the engine code affected the predicted steady state operation as well as making spool accelerations more sluggish and raising compressor working lines during transient manoeuvres. Although all three effects were significant, heat soakage appeared to have the largest effect on transient performance, particularly during the hot reslam manoeuvre. Rolls-Royce PLC sponsored this EngD project laying down 5 project requirements that enhanced heat soakage and tip clearance methods should meet, i.e. handle both heat soakage and tip clearances, be physics based, run at or near to real time, meet given accuracy targets, and be capable of being calibrated. The streams method met the first three of these requirements, although with further development it might be possible to meet all five. This thesis also contains analysis and recommendations regarding the process of technology transfer from the Cranfield University Technology Centre in Gas Turbine Performance to within Rolls-Royce.